2021
DOI: 10.3389/fimmu.2021.654872
|View full text |Cite
|
Sign up to set email alerts
|

dmLT Adjuvant Enhances Cytokine Responses to T Cell Stimuli, Whole Cell Vaccine Antigens and Lipopolysaccharide in Both Adults and Infants

Abstract: Enhancement of mucosal immune responses in children and infants using novel adjuvants such as double mutant heat labile toxin (dmLT) is an important goal in the enteric vaccine field. dmLT has been shown to enhance mucosal IgA responses to the oral inactivated enterotoxigenic Escherichia coli (ETEC) vaccine ETVAX. dmLT can enhance IL-17A production from adult T cells, which may increase the production and secretion of mucosal IgA antibodies. However, the adjuvant mechanism remains to be fully elucidated and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Seventy-eight (56%) of 139 infants aged 6-11 months who were vaccinated developed mucosal responses against at least three of the vaccine antigens versus 14 (29%) of 49 of the infants given placebo. Addition of the adjuvant dmLT enhanced the magnitude, breadth, and kinetics (based on number of responders after the first dose of vaccine) of immune responses in infants (19). A similar positive dmLT effect was observed on the mucosal antibody response in the 12-23 month age group in this study when the antigenic breath of the responses was considered.…”
Section: Use Of An Adjuvant To Maximize Immune Responses In Vaccine T...supporting
confidence: 78%
“…Seventy-eight (56%) of 139 infants aged 6-11 months who were vaccinated developed mucosal responses against at least three of the vaccine antigens versus 14 (29%) of 49 of the infants given placebo. Addition of the adjuvant dmLT enhanced the magnitude, breadth, and kinetics (based on number of responders after the first dose of vaccine) of immune responses in infants (19). A similar positive dmLT effect was observed on the mucosal antibody response in the 12-23 month age group in this study when the antigenic breath of the responses was considered.…”
Section: Use Of An Adjuvant To Maximize Immune Responses In Vaccine T...supporting
confidence: 78%
“…Vaccine preparation with dmLT has been found to be effective against mucosal infections. It has been concluded that dmLT will be useful to overcome hypo-responsiveness to other whole cell-or LPSbased vaccines such as cholera, Salmonella typhi, and Shigella vaccines in infants in economically less developed countries (215). We predict that the use of dmLT in vaccine preparations for infants will be highly effective in the future.…”
Section: Discussionmentioning
confidence: 98%
“…CTB (e.g., Dukoral ® vaccine), the Escherichia coli LT subunit B (LTB), or double mutant LT (dmLT) are also promising mucosal adjuvants to trigger specific Th17 immune responses. CTB as adjuvant has been almost evaluated fused to the vaccine antigen 72–75 . In addition to CTB, LTB and dmLT, recent adjuvant alternatives have been also evaluated such as mucosal administration of cyclic dinucleotides, 75 suggesting that the stimulation of mucosal H. pylori ‐specific Th17 responses could be envisioned in the future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…CTB as adjuvant has been almost evaluated fused to the vaccine antigen. 72 , 73 , 74 , 75 In addition to CTB, LTB and dmLT, recent adjuvant alternatives have been also evaluated such as mucosal administration of cyclic dinucleotides, 75 suggesting that the stimulation of mucosal H. pylori ‐specific Th17 responses could be envisioned in the future clinical trials.…”
Section: Discussionmentioning
confidence: 99%